An ecogeographic study African vigna - Maxted, N.; Mabuza-Diamini, P.; Moss, H.; Padulosi, S.; Jarvis, A.; Guarino, Luigi (2004)
An ecogeographic study of cowpea and Bambara groundnut and their wild relatives (Vigna Savi) in Africa is presented; as circumscribed, the African taxa comprise 61 species and 63 subspecific taxa. The taxonomy, genetic diversity and use of wild and cultivated African Vigna, as well as the African phytogeographic context and threats to plant diversity, are reviewed. Ecogeographic data were recorded for each taxon throughout its geographical range within Africa. Representative herbarium specimens and genebank accessions were each identified and passport data collated into the ecogeographic database from thirty herbaria and four genebanks in Africa, Europe and North America. These specimen passport data were supplemented by field observation and taxon-based information from the literature. An assessment of current ex situ and in situ conservation status of wild and cultivated Vigna species in Africa is made. The African Vigna ecogeographic database contains the “raw” phytogeographic, ecological, genetic and taxonomic data for 7289 herbarium specimens and 1802 genebank accessions representing the 61 species sampled between 1762 and 1997. These data are summarized for each taxon in the ecogeographic conspectus. The conspectus includes: accepted names of taxa, author(s), date of publication, where published; reference to full description and iconography; botanical illustrations; vernacular names; habit and lifespan; flower colour; habitat; associated species; altitude range; geographical distribution, actual distribution and predicted distribution maps; phenology and uses; as well as individual taxon vulnerability assessment; conservation notes; IUCN Red List Category; taxonomic notes and other additional notes.General patterns of taxonomy, phytogeography and ecology for African Vigna are discussed following detailed ecogeographic and spatial biogeographic analyses using geographic information systems (GIS). The climatic characteristics underlying the distribution and species richness of Vigna in Africa is reported. Many taxa have not been or are poorly represented in ex situ collections. Analysis of species distribution patterns showed a high correlation (=0.748) between levels of species richness and rarity. Vigna is shown to have a broad distributional range across the African continent south of the Sahara and north of 30° south, being most rich in subtropical latitudes around 10° north and south. Three hotspots of Vigna diversity were found: around the Great Lakes, the southern tip of Lake Tanganyika and the Cameroon Highlands. Models that predict species richness have highlighted other areas with potentially higher species richness that are undersampled in the Democratic Republic of the Congo, south of Lake Victoria in Tanzania, and in central Togo. Based on an analysis of complementary areas, just three grid cells contain 37 species. Specific conservation actions are recommended. It is suggested that: in situ genetic reserves are established within existing protected areas at the southern tip of Lake Tanganyika, in the coastal area of Sierra Leone and between Lake Victoria and the other Great Lakes; there is a need to establish patterns of genetic diversity in landraces of V. subterranea and V. unguiculata before in situ on-farm conservation can be proposed; and further germplasm collection and ex situ conservation are particularly required in Cameroon, the Democratic Republic of the Congo, Guinea Bissau, Nigeria and Zambia and V. dolomitica, V. haumaniana var. pedunculata, V. monantha, V. nuda, V. richardsiae, V. somaliensis, V. stenophylla, V. subterranea var. spontanea, V. unguiculata subsp. unguiculata var. spontanea, V. unguiculata subsp. aduensis, V. unguiculata subsp. baoulensis, V. unguiculata subsp. burundiensis, V. vexillata var. dolichonema and V. virescens are the highest priority species. Future research requirements to ensure sustainable conservation and use of African Vigna genepools are discussed.